THE INFLUENCE OF PARENTAL NEGLIGENCE ON THE EMOTIONAL STATE OF THE CHILD (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
This article describes how the indifferent attitude of parents towards a child in the family negatively affects the mental state of the child. As a result of parents' neglect of the child's needs, due to lack of care for him, the child's emotional state is disturbed; such an attitude poses a threat to the health or mental development of the child. Some recommendations are also given for working with mental disorders in the child's psyche.